STRUKTUR KOMUNITAS FITOPLANKTON DI DANAU OPI JAKABARING KOTA PALEMBANG - Eddy, Syaiful (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2015)
Research on the Structure of Phytoplankton in Lake OPI Jakabaring Palembang was held in January 2015 in the Lake District of Seberang Ulu OPI 1 Palembang, aims to determine the structure and composition of phytoplankton communities are didanau OPI Jakabaring. This study used a survey method. Phytoplankton samples were taken from three stations, namely middle, upstream and downstream in the lake OPI Jakabaring Palembang. Then performed and identification of the type and amount of phytoplankton from each lake water samples were taken. Physical and chemical parameters measured in field waters that include brightness, depth, temperature, DO and pH. Results showed that the community structure of phytoplankton in lakes OPI Jakabaring consists of 18 species of phytoplankton. The abundance of phytoplankton with the lowest density value between Â 28.75ind/l - 55.375ind/l. Diversity index of the three observation stations is low with the Hâ 0,201-0,307.Â Key words: community structure, phytoplankton, water quality